FEATURES OF THE UZBEK DASTAN ART (Scientific journal of the Fergana State University, 2023)
The article discusses the features of the Uzbek dastan art. The author explains in detail the pedagogical traditions of Uzbek storytelling, highlighting the specific aspects of this centuries-old art. The article claims that the features of different dastan schools are related to common epic traditions.